Variable impact on mortality of AIDS-defining events diagnosed during combination antiretroviral therapy: not all AIDS-defining conditions are created equal. - Mocroft, Amanda; Sterne, Jonathan A C; Egger, Matthias; May, Margaret; Grabar, Sophie; Furrer, Hansjakob; Sabin, Caroline; Fatkenheuer, Gerd; Justice, Amy; Reiss, Peter; d'Arminio Monforte, Antonella; Gill, John; et al. (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2009)
The extent to which mortality differs following individual acquired immunodeficiency syndrome (AIDS)-defining events (ADEs) has not been assessed among patients initiating combination antiretroviral therapy.
Keywords: Acquired Immunodeficiency Syndrome; Adult; AIDS-Related Opportunistic Infections; Anti-HIV Agents; Cohort Studies; Drug Therapy, Combination; Female; Humans; Lymphoma, AIDS-Related; Male; Prognosis; Proportional Hazards Models